Bagaimana Pedagang Muslim Istiqomah Dalam Kejujuran? - Purnomo Adji; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The aim of this research is to find out and understand the integrity of muslim traders in honesty (ash-shidqu) while doing their job. This research uses explanatory qualitative case study approach. Data collection was done by doing interviews and documentation towards the research objects who were three convenience store merchants in Tenggilis area in Surabaya. The result is the istiqomah (having integrity) attitude of the merchants are classified into to aspects which are material and religiosity. The thing behind their actions to be istiqomah in honesty is their fear towards Allah SWT and the impact that will come up if they are not dishonest and unjustifiable in doing their trade.